THE WOMAN EMOTION LEVEL IN TO FACE IN MENOPAUSE IN JORONG BATU AJUNG KECAMATAN SIJUNJUNG - Chia, Velia Nesis; Kasih, Fitria; Zaini, Ahmad (Bimbingan dan Konseling, 2013)
This Problems based on the phenomenon that researchers found in the field was how the woman emotion level in to face of menopause in batu ajung, Sijunjung. This research aimed to describe: the woman emotion level in to face of menopause seen from the level ofÂ positive and negative emotions in the face of female menopause. This research was a descriptive research that try to describe the way thing are. The population in this research was middle adult women who face menopause in batu ajung, sijunjung. Sampling in this research using purposive sampling so the sample size was 34 people. Instrument used in this research was a questionnaire. While for data analysis usedÂ percentage technique.The research results revealed that: the woman emotion level in to face of menopause in batu ajung, sijunjung views from positive emotion level, was inÂ category low level, and the woman emotion level in to face in menopause in batu ajung, sijunjung seen from negative emotions level includes the high category.